Layered beam vibrations including slip - Henghold, William Murray, author; Department of Civil Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1972)
This study presents a theory for vibrations of layered beams with the effects of interlayer slip included. The theory is developed using Bernoulli-Euler assumptions with additional developments to account for the interlayer movement. The development is general, in the small deflection sense, for beams with mechanical connections. The development leads to governing equations for beams having both dual and single axes of symmetry and an arbitrary number of layers. Solutions to the governing equations are presented in closed form for various sets of boundary conditions. These solutions show the effect of interlayer connection on the natural frequency, and it is shown that the solutions reduce to well known values for the extremes of interlayer connection. The effect of damping on the solutions is presented, and the equations for the damped system are solved for small damping. The results of some simple tests which were performed are presented, and these results are shown to agree favorably with the proposed theory.
Also issued as author's dissertation.
Series numbering taken from cover.
Keywords: Girders -- Vibration; Structural analysis (Engineering)